Geographical Analysis of Climate Supplies of Summer Vegetables in The Dukan District (Raparin Journal of Humanities (RJH), 2025)
Summer vegetables are one of the most important agricultural products, from food, health and economy for humans. Summer vegetables are under some factors of nature and humanity. Among the natural factors, climate is the most significant factor for growing and dividing agricultural products. The most important climate element is temperature, which has an effect on the quantity and quality of crops and other climate elements, directly and indirectly. The aim of this research is to indicate the efficiency of the climate for vegetables and their adaptation of the climate capacities in the study area. descriptive and analysis methods are used to describe significant kinds of summer vegetables with analysis of climate data during a study for thirty (30) years in the study area. And the comparative method is used to indicate these changes in the climate data that are effects on bringing forward and backward cultivation of crops. In the end, we have some results; the most significant are: Summer vegetables in the first stage of growing need more sunlight at rate (2% - 3%) compared to other stages. Each of the pepper, eggplant, and watermelon crops are not planted at the right time, so germination and growth are delayed in the study area, but each of the tomato, okra, and cucumber crops have their cultivated times convenient with climate supplies.